THE INFLUENCE OF ORGANIZATIONAL SUPPORT, REWARDS, EMPOWERMENT AND TRAINING ON JOB SATISFACTION OF EMPLOYEES AT RSU CUT MEUTIA LHOKSEUMAWE - Najlun Fariha; Yusniar; Yanita; Aiyub Yahya (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This research was conducted to examine the extent of the direct influence of Organizational Support, Rewards, Empowerment and Training on Employee Job Satisfaction in a hospital. The purpose of this research is to determine the level of job satisfaction of employees who work at RSU Cut Meutia Lhokseumawe. Therefore, research was conducted using data that had been collected through direct or manual surveys with a sample size of 100 employees. To analyze the collected data, SPSS and multiple linear regression were used. The research results show that the Organizational Support variable has no effect on Employee Job Satisfaction. Meanwhile, the Reward variable has a positive and significant effect on Employee Job Satisfaction. It was also found that the Empowerment variable had a positive and significant effect on Employee Job Satisfaction. Furthermore, the Training variable has a positive and significant effect on Employee Job Satisfaction. These findings provide useful implications for policy makers to determine strategies related to human resource factors to increase employee job satisfaction.